Tailoring DNA Vaccines: Designing Strategies Against HER2-Positive Cancers - Marchini, Cristina; Kalogris, Cristina; Garulli, Chiara; Pietrella, lucia; Gabrielli, Federico; Curcio, Claudia; Quaglino, Elena; Cavallo, Federica; Amici, Augusto (Frontiers in Oncology, 2013)
The crucial role of HER2 in epithelial transformation and its selective overexpression on cancer tissues makes it an ideal target for cancer immunotherapies such as passive immunotherapy with Trastuzumab. There are, however, a number of concerns regarding the use of monoclonal antibodies which include resistance, repeated treatments, considerable costs and side effects that make active immunotherapies against HER2 desirable alternative approaches. The efficacy of anti-HER2 DNA vaccination has been widely demonstrated in transgenic cancer-prone mice, which recapitulate several features of human breast cancers. Nonetheless, the rational design of a cancer vaccine able to trigger a long lasting immunity, and thus prevent tumor recurrence in patients, would require the understanding of how tolerance and immunosuppression regulate antitumor immune responses and, at the same time, the identification of the most immunogenic portions of the target protein. We herein retrace the findings that led to our most promising DNA vaccines that, by encoding human/rat chimeric forms of HER2, are able to circumvent peripheral tolerance. Preclinical data obtained with these chimeric DNA vaccines have provided the rationale for their use in an ongoing phase I clinical trial (EudraCT 2011-001104-34).